2010
DOI: 10.1007/s12262-010-0163-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Radical vs. Conservative Surgical Treatment of the Hepatic Hydatid Cyst: A 10-Year Experience

Abstract: The hepatic hydatid cyst is a major health problem in endemic areas. Surgery is still the best choice for the treatment of hydatid cyst of the liver. There is controversy regarding efficacy of radical versus conservative surgical approaches. In this study, we aimed to evaluate the two surgical methods in patients treated for the hepatic hydatid cyst. This is a retrospective review of the medical records of 135 patients who underwent surgery for the hepatic hydatid cyst from 1993 to 2003. Surgery comprised cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…The mortality rate was similar to that reported in the literature (1·2 per cent, ranging from 0 to 6·5 per cent). There was no statistical difference in overall morbidity or deep abdominal complications between the conservative and radical groups, and rates were in the range reported in the literature (10–29·5 per cent).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The mortality rate was similar to that reported in the literature (1·2 per cent, ranging from 0 to 6·5 per cent). There was no statistical difference in overall morbidity or deep abdominal complications between the conservative and radical groups, and rates were in the range reported in the literature (10–29·5 per cent).…”
Section: Discussionsupporting
confidence: 86%
“…Patients with either of these were excluded from the present study. This may partly explain differences in recurrence rates compared with published values for the conservative approach to treatment of liver hydatid cysts. These studies reported a higher recurrence rate for the conservative surgical approach.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations